Addressing rural and remote access disparities for patients with inflammatory arthritis through video‐conferencing and innovative inter‐professional care models. (2nd October 2017) - Taylor‐Gjevre, Regina; Nair, Bindu; Bath, Brenna; Okpalauwaekwe, Udoka; Sharma, Meenu; Penz, Erika; Trask, Catherine; Stewart, Samuel Alan
Abstract: Objective: The aim of the present study was to evaluate whether rheumatoid arthritis (RA) patients followed longitudinally using video‐conferencing and inter‐professional care support have comparable disease control to those followed in traditional in‐person rheumatology clinics. Methods: This was a randomized controlled trial for 85 RA patients allocated to either traditional in‐person rheumatology follow‐up or video‐conferenced follow‐up with urban‐based rheumatologists and rural in‐person physical therapist examiners. Follow‐up was every 3 months for 9 months. Outcome measures included disease activity metrics (disease activity in 28 joints with CRP measure score [DAS28‐CRP], and RA disease activity index [RADAI]), modified health assessment questionnaire (mHAQ), quality of life (EuroQOL five dimensions questionnaire [EQ5D]) and patient satisfaction (nine‐item visit‐specific satisfaction questionnaire [VSQ9]). Results: Of 85 participants, 54 were randomized to the video‐conferencing team model and 31 to the traditional clinic (control group). Dropout rates were high, with only 31 (57%) from the video‐conferencing and 23 (74%) from the control group completing the study. The mean age for study participants was 56 years; 20% were male. Mean RA disease duration was 13.9 years. There were no significant between‐group differences in DAS28‐CRP, RADAI, mHAQ or EQ5D scores at baseline or over the study period. Satisfaction rates were high in both groups. Conclusions: We found no evidence of a difference in effectiveness between inter‐professional video‐conferencing and traditional rheumatology clinic for both the provision of effective follow‐up care and patient satisfaction for established RA patients. High dropout rates reinforce the need for consultation with patients' needs and preferences in developing models of care. While use of video‐conferencing/telehealth technologies may be a distinct advantage for some patients, there may be loss of travel‐related auxiliary benefits for others.